2004
DOI: 10.1007/s00586-004-0754-9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative erythropoietin in spine surgery

Abstract: IntroductionSurgery for spinal deformities or degenerative lumbar disease may be associated with blood loss ranging from 30% to 100% of the patient's total blood volume [18, 26,68,79,85,87]. This loss of blood is related to the complexity of the procedure, duration of surgery, number of fused levels, anaesthetic technique and the patient's comorbid conditions [18, 26,68,76,79,85,87]. Extensive bleeding may lead to rapid fatal consequences and to risks associated with allogenic blood transfusion [4, 8, 36,40,81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 72 publications
(77 reference statements)
0
12
0
1
Order By: Relevance
“…In conclusion, EPO is a pluripotent growth factor that seems worthwhile investigating for its osteogenic and angiogenic potencies in the field of orthopedics. In the future, EPO may fill a gap in orthopedic surgery as a graft enhancer, if bone harvest is needed but insufficient and a high blood loss is anticipated in the management of both anemic and normal patients 27–29…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, EPO is a pluripotent growth factor that seems worthwhile investigating for its osteogenic and angiogenic potencies in the field of orthopedics. In the future, EPO may fill a gap in orthopedic surgery as a graft enhancer, if bone harvest is needed but insufficient and a high blood loss is anticipated in the management of both anemic and normal patients 27–29…”
Section: Discussionmentioning
confidence: 99%
“…In a review of their blood conservation program for spine surgery, Colomina et al. (61) observed that the use of preoperative erythropoietin alone allowed for a higher preoperative hematocrit compared to patients in the PAD program. Neither group required intraoperative ABT.…”
Section: Alternatives To Blood Transfusionsmentioning
confidence: 99%
“…More than 50% of such patients require additional allogenic blood transfusions [1,2]. The goal of preoperative administration of recombinant human erythropoietin (rHu-EPO) is to increase erythropoiesis in patients who are donating blood for autologous use and therefore decrease the need for allogenic transfusions [3,4]. Previous reports found that the pharmacological response to erythropoietin therapy is a function of dose and administration regimen and that repeated administration of rHu-EPO is more effective in stimulating the reticulocyte response than is single-dose administration of the same total amount of rHu-EPO [5].…”
Section: Introductionmentioning
confidence: 99%